2014
DOI: 10.1371/journal.pone.0107988
|View full text |Cite
|
Sign up to set email alerts
|

Galectin Expression Profiling Identifies Galectin-1 and Galectin-9Δ5 as Prognostic Factors in Stage I/II Non-Small Cell Lung Cancer

Abstract: Approximately 30–40% of the patients with early stage non-small cell lung cancer (NSCLC) will present with recurrent disease within two years of resection. Here, we performed extensive galectin expression profiling in a retrospective study using frozen and paraffin embedded tumor tissues from 87 stage I/II NSCLC patients. Our data show that galectin mRNA expression in NSCLC is confined to galectin-1, -3, -4, -7, -8, and -9. Next to stage, univariable Cox regression analysis identified galectin-1, galectin-9FL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…The involvement of galectins in different processes of tumor progression is supported by reports that altered galectin expression has diagnostic or prognostic value in different cancer types including ovarian, prostate, breast, head and neck and non-small cell lung cancer [1726]. In squamous cervical cancer patients who received radiation therapy, a recent study reported that expression of galectin-1 by the tumor was an independent predictor for local recurrence and poor survival [27].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of galectins in different processes of tumor progression is supported by reports that altered galectin expression has diagnostic or prognostic value in different cancer types including ovarian, prostate, breast, head and neck and non-small cell lung cancer [1726]. In squamous cervical cancer patients who received radiation therapy, a recent study reported that expression of galectin-1 by the tumor was an independent predictor for local recurrence and poor survival [27].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, such valuable information is not obtained by analysis of gene expression at the mRNA level. On the other hand, single nucleotide polymorphisms as well as alternative splice variants of specific galectins have also been associated with prognosis . Such variations are not always detected by the currently available antibodies, an observation that indicates the relevance of combining both genomic and proteomic information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deregulated expression or function of galectin‐1 is frequently associated with disease, most notably with inflammatory disorders and cancer . Regarding the latter, we and others have shown that increased galectin‐1 expression is associated with poor survival in many cancer types . This has been attributed to the capacity of galectin‐1 to suppress the anti‐tumor immune response, to induce tumor angiogenesis, and to promote tumor metastasis .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations